- (Journal of Sciences, Islamic Republic of Iran)
X-ray diffraction measurements were performed on Co?Pt1-?/Pd, Co/Pd, Co/Fe, and Co/W multilayer samples with different structures, such as Co?Pt1-? alloy layer composition ?, bilayer thickness, and number of bilayers. Multilayer samples were made by magnetron sputtering in a chamber with multi-parallel guns and a position controllable substrate. Co?Pt1-? alloy layers were deposited by cosputtering from Co and Pt targets mounted on guns tilted towards a common substrate. Compositions of Co and Pt in Co?Pt1-? layers were varied by use of different sputtering power. The thicknesses of magnetic and non-magnetic layers in multilayered samples were also systematically changed to investigate the relationship between X-ray diffraction lines and crystalline structures of multilayered films. It was found that the position of the main diffraction peak from multilayered films was solely determined by the crystalline structures within bilayers rather than bilayer thickness. A model was introduced to calculate microstructural parameters such as the thickness of interfaces and compositions at interfaces.